MESENCHYMAL STEM CELLS: A REGENERATIVE HOPE FOR ALZHEIMER’S PATIENTS - Rehab H Abdel-Aziz, Omyma Galal Ahmed, Abeer Madkour Mahmoud, Hanan H Abd-Elhafeez, Lamiaa Abd-Elsamiee, Rana Toghan (Chelonian Research Foundation, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, memory impairment, and neuronal loss. Despite extensive research, effective disease-modifying therapies remain limited. Mesenchymal stem cells (MSCs) have emerged as a promising therapeutic candidate due to their multipotent properties, immunomodulatory capacity, and ability to secrete neurotrophic factors. This review explores various aspects of AD, as well as it explores MSCs mechanisms of action including reduction of neuroinflammation, promotion of neurogenesis, clearance of amyloid-β plaques, and protection against oxidative stress. We also discuss the various sources of MSCs, and methods of delivery.